Perfect passwords selection, protection, authentication - Burnett, Mark.; Kleiman, Dave. (Rockland, Mass. : Syngress, 2006)
User passwords are the keys to the network kingdom, yet most users choose overly simplistic passwords (like password) that anyone could guess, while system administrators demand impossible to remember passwords littered with obscure characters and random numerals. Every computer user must face the problems of password security. According to a recent British study, passwords are usually obvious: around 50 percent of computer users select passwords based on names of a family member, spouse, partner, or a pet. Many users face the problem of selecting strong passwords that meet corporate security requirements. Too often, systems reject user-selected passwords because they are not long enough or otherwise do not meet complexity requirements. This book teaches users how to select passwords that always meet complexity requirements. A typical computer user must remember dozens of passwords and they are told to make them all unique and never write them down. For most users, the solution is easy passwords that follow simple patterns. This book teaches users how to select strong passwords they can easily remember. * Examines the password problem from the perspective of the administrator trying to secure their network * Author Mark Burnett has accumulated and analyzed over 1,000,000 user passwords and through his research has discovered what works, what doesn't work, and how many people probably have dogs named Spot * Throughout the book, Burnett sprinkles interesting and humorous password ranging from the Top 20 dog names to the number of references to the King James Bible in passwords.
Passwords : the basics and beyond -- Meet your opponent -- Is random really random? -- Character diversity : beyond the alphabet -- Password length : making it count -- Time : the enemy of all secrets -- Living with passwords -- Ten password pointers : building strong passwords -- The 500 worst passwords of all time -- Another ten password pointers plus a bonus pointer -- The three rules for strong passwords -- Celebrate password day -- The three elements of authentication.
Keywords: Computers -- Access control -- Passwords; Electronic books